Menjaga Tanah Leluhur: Aliansi Masyarakat Adat Nusantara di Sulawesi Selatan 2003-2016 - Kamaruddin Kamaruddin; Najamuddin Najamuddin; Patahuddin Patahuddin (PATTINGALLOANG, 2017)
This study reveals that the background of the awakening of indigenous peoples in South Sulawesi, due to the marginalization of the state policy with agrarian resources pengulaaan that began in 1811 in the colonial period and the 1999 era of reform that led to agrarian conflicts. Indigenous peoples in South Sulawesi formed a strength by organizing their groups into AMAN formed in 2003. The organizational development has experienced three successive organizational leaders namely MahirTakaka at the beginning of the formation of 2003-2008 which was appointed Sirajuddin at the first muswil 2008-2013 and then SardiRasak on the second muskil 2013-2016. In making AMAN a struggle organization, the strategy of struggle by taking three paths of organizational education, political struggle and lane of litigation. This research is a historical research with historical methodology that has stages, heuristics (data collection), criticism (verification), interpertasi (interpretation) and historiography (historical writing). This research is a historical research with historical methodology that has stages, heuristics (data collection), criticism (verification), interpertasi (interpretation) and historiography (historical writing).